Karighor: arts and crafts for rural development - Arif, Nuzhat; Zohora, Fatema Tuz (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.